Teacher burnout: relations between dimensions of burnout, perceived school context, job satisfaction and motivation for teaching. A longitudinal study. Issue 7 (16th November 2020) - Skaalvik, Einar M.; Skaalvik, Sidsel
ABSTRACT: The purpose of this longitudinal study was to analyse relations between teachers' perceptions of job demands and job resources in the school environment and dimensions of burnout, depressed mood, job satisfaction and motivation to leave the teaching profession (quit). The participants were 262 Norwegian high school teachers. The teachers' perceptions of three job demands (time pressure, low student motivation, and dissonant value context) and two job resources (autonomy and supervisory support) were measured at time 1 (September) whereas burnout, depressed mood, job satisfaction and motivation to leave the teaching profession were measured at time 2 (April). The data were analysed by means of confirmatory factor analysis and SEM analysis. The job demands and the job resources that were included in the study related differently to the three dimensions of burnout (emotional exhaustion, cynicism, and self-perceived accomplishment) and the dimensions of burnout related differently to measures of depressed mood, job satisfaction, and motivation to quit. For instance, time pressure was the strongest predictor of emotional exhaustion whereas low student motivation and working in a dissonant value context were the strongest predictors of cynicism. Also, autonomy was positively associated with self-perceived accomplishment whereas low student motivation was negatively associated with self-perceived accomplishment.